2008
DOI: 10.1074/jbc.m801967200
|View full text |Cite
|
Sign up to set email alerts
|

Root-Microbe Communication through Protein Secretion

Abstract: Biotic interactions in the rhizosphere are biologically important, and although many of those interactions have been well studied, the role of secreted proteins in the cross-talk between microbes and roots has not been investigated. Here, protein secretion was studied during the communication between the roots of two plants (Medicago sativa and Arabidopsis thaliana) and the bacterial symbiont of one of these species (Sinorhizobium meliloti strain Rm1021) and an opportunistic bacterial pathogen of A. thaliana (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(157 citation statements)
references
References 88 publications
(79 reference statements)
2
153
0
2
Order By: Relevance
“…This could be due to the fact that root exudates were collected in vitro while rhizosphere microbial communities were analyzed in vivo; in other words, the root secretion patterns could be different under soil conditions. Accordingly, it has been reported that under in vitro conditions plants grown alone or cocultured with a microorganism show different patterns of proteins present in the root exudates (De-la-Pena et al, 2008). However, Chaparro et al (2013) showed evidence that root exudation through development is genetically programmed since there were strong correlations between in vitro root exudation patterns and the ability of the soil microbiome to utilize these compounds in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that root exudates were collected in vitro while rhizosphere microbial communities were analyzed in vivo; in other words, the root secretion patterns could be different under soil conditions. Accordingly, it has been reported that under in vitro conditions plants grown alone or cocultured with a microorganism show different patterns of proteins present in the root exudates (De-la-Pena et al, 2008). However, Chaparro et al (2013) showed evidence that root exudation through development is genetically programmed since there were strong correlations between in vitro root exudation patterns and the ability of the soil microbiome to utilize these compounds in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…lycopersici (Jones et al, 1972;Lafitte et al, 1984;Powell et al, 2000). These proteins also have been found in the secretome of Arabidopsis roots when the plant is infected with P. syringae (Magro et al, 1994;De-la-Peña et al, 2008), which indicates that PGIPs participate in defense response signaling in the rhizosphere during bacterial attack. Therefore, PGIPs could be exploited as a strategy for protecting crops against PG-producing pathogens.…”
Section: Pgsmentioning
confidence: 83%
“…There are data that strongly suggest that changes in protein secretion could be due to epigenetic changes. For instance, De-la-Peña et al (2008, 2010, working with Arabidopsis defense-impaired mutants nonexpressor of PATHOGENESIS-RELATED GENES1 (npr1-1; a mutant that does not express NPR1), constitutive expressor of PATHOGENESIS-RELATED GENES5 (cpr5-2; a mutant that accumulates large amounts of salicylic acid), and salicylate hydrolase (NahG; a mutant that is unable to accumulate salicylic acid), found that these mutants had a different protein root secretion pattern. Moreover, it was found that the defense-responsive genes in Arabidopsis, like CPR5 and NPR1, could be mediated by epigenetic factors (De-la-Peña et al, 2012c), suggesting that protein root secretion also could be modified due to epigenetic changes.…”
Section: Epigenomicsmentioning
confidence: 99%
“…Furthermore, protein patterns released as root exudates depend on the identity of microorganisms exposed to the roots of A. thaliana [222]. Pseudomonas syringae, an A. thaliana pathogen, highly induced secretion (from A. thaliana) of defense proteins, such as peroxidases, glycosyl hydrolase family 17, chitinase, and glycosyl hydrolase family 18 [222].…”
Section: Root Exudation the Ecological Driver Of Microbial Communitimentioning
confidence: 99%
“…Proteins secreted by roots are important for recognition of pathogenic and non-pathogenic bacteria [221,222]. For example, lectins function as defense factors and recognition in symbiotic interactions [223].…”
Section: Root Exudation the Ecological Driver Of Microbial Communitimentioning
confidence: 99%